Tradisi Lokal dan Kehidupan Masyarakat Melayu Jambi Di Kawasan Jambi Kota Seberang - Karmela, Siti Heidi; Yanto, Ferry (Jurnal Ilmiah Dikdaya, 2022)
This research is a historical research with the theme of cultural history that seeks cultural morphology, studies of structure, central concepts, developments and changes in certain societies, including traditions. Therefore, the purpose of this study is to explain the existence of traditions in the life of the Jambi Malay community which are socio-religious and social in the Jambi area of the opposite city and start from their growth, development to preservation, as well as the noble values contained in these traditions. Meanwhile, the research method is the historical method by following the stages of heuristics, criticism, interpretation, and historiography.The conclusion of the study shows that there are two types of traditions that are still preserved by the Jambi Malay community in the Jambi area of the opposite city, namely socio-religious (Nisfu Sya'ban, Burdah, Assyura, Barzanji, Syuro) and social society (Nuak, Nginau, Nyukur Baby, Makan Besamo, Grave pilgrimage). This tradition is closely related to Islamic values, passed down from generation to generation and taught the procedures by Tuan Guru.The findings during the research were changes in the meaning and implementation of existing traditions due to various factors, furthermore the fact that the tradition still has values that are realized in the lives of people in Jambi kota seberang.Â